Evaluation of cardiometabolic function with serum adropin levels in psoriasis patients (Annals of Medical Research, 2021)
Aim: Psoriasis is a skin disease with metabolic and cardiac comorbidities. Adropin is a peptide hormone which is thought to play arole in metabolic diseases, energy homeostasis, endothelial function and cardiac diseases in recent years. In this study, we aimed toevaluate adropin levels in psoriasis patientsMaterials and Methods: The study included 51 plaque psoriasis patients aged 18-65 years who had no systemic disease and hadnot received systemic treatment in the last three months and 37 healthy controls matched by sex, age and body mass index (BMI).Serum adropin, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), andtriglyceride (TG), fasting blood glucose (FBG), fasting serum insulin, BMI, systolic blood pressure (SBP) and diastolic blood pressure(DBP) values were recorded.Results: Serum adropin level was 73.04 ± 46.21 pg / ml in the patient group. In the control group, serum adropin level was 77.26 ±43.69 pg / ml. Serum adropin levels were lower in the patient group, but this was not statistically significant (p = 0.667). PASI valuewas negatively correlated with serum adropin level. There was no correlation between serum adropin level and other variables.Insulin level, Homa-IR level, systolic and diastolic pressure were significantly higher in the patient group (p
Keywords: Adropin; cardiometabolic function; PASI; psoriasis